Strategi Bank Indonesia Untuk Meretas Jaringan Money Changer Ilegal - Kurniawati, Alfani Dewi; Wati, Lisa; Rohman, Taufiqur (CV. Kurnia Grup, 2024)
The purpose of writing this article is to find out what Bank Indonesia strategies can be used to hack illegal money changer networks in order to secure the circulation of foreign currency in Indonesia. The research method used is descriptive qualitative with a literature review approach used to investigate and synthesize previously published findings regarding the research topic. There are 4 strategies that can be implemented to crack down on illegal money changers, namely strengthening regulations regarding official money changers, educating the public about the importance of using legal and registered money changer services, international cooperation and providing rewards to legal money changers. Through strengthening supervision, outreach to the public, international cooperation, and providing incentives for legal money changers, Bank Indonesia is trying to suppress illegal activities that have the potential to damage the country's financial stability. With coordinated and continuous efforts, it is hoped that the circulation of illegal foreign currency can be minimized so that the country's financial stability can be well maintained.